X/Y shaped periorbital reconstructive surgery following enucleation or exenteration in dogs and cats: 24 cases (2013–2020). (15th February 2021) - Vlachomitrou, I. E.; Cinti, F.; Kumaratunga, V.; Nuti, M.; Pisani, G.
Abstract : Objectives: To describe the X/Y shaped periorbital reconstruction technique following enucleation or exenteration in dogs and cats and to evaluate its cosmetic and functional results. Materials and Methods: Medical records of dogs and cats from two different institutions that required enucleation or exenteration, followed by an additional X or Y plasty using fibrous periorbital tissue for cosmetic reasons, were retrospectively reviewed. All patients were evaluated clinically at 1–2 weeks, 2 months and 6 months. The eyelid sinking was scored as absent or present. Results: Nineteen dogs and five cats were included in the study. Twelve dogs and three cats had an enucleation, while the remaining seven dogs and two cats underwent exenteration. In the short‐term follow up, three patients had periorbital oedema. Sixty days and 6 months post‐surgery, two cats and two dogs showed eyelid depression. These two dogs were both dolichocephalic breeds. The rest of the patients showed no eyelid sinking, while the periorbital oedema observed in the short‐term follow up in the two dogs and one cat had completely resolved. The four patients with ocular neoplasia did not have the 6 months follow up, because of fatal metastatic disease or euthanasia. Clinical Significance: The X/Y periorbital reconstructive procedure is quick, easy to perform and it provided satisfying long‐term cosmetic results, except for four cases that developed eyelid depression.